IMPORTANCE OF COMPETENT BASED APPROACH SO AS TO IMPROVE STUDENTS’ SPEAKING SKILLS AT HIGHER EDUCATION - Abdukhakimova Kamola Akmalovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
One of the main objectives of foreign language instruction in higher education institutions is the improvement of students’ speaking abilities. However, conventional education approaches frequently place more emphasis on theoretical understanding than on real-world language application. In this sense, the competency-based approach has drawn a lot of attention as a successful strategy for fostering communicative competence. This study aims to evaluate the significance of the competency-based approach in enhancing students’ speaking abilities in postsecondary educational settings. The study investigates how competency-based learning improves students’ capacity for critical thought, effective communication, and practical application of language knowledge. The competency-based framework looked at a variety of instructional techniques, such as role plays, interactive exercises, conversations, and problem-solving assignments. The results show that students’ interest, engagement, and confidence in speaking a foreign language are greatly increased by the competency-based approach. Additionally, it encourages self-directed learning and assists students in acquiring the practical communication skills required for both academic and professional settings. The findings imply that students’ speaking skill can be significantly increased by incorporating competency-based teaching techniques into foreign language learning. Therefore, in order to educate students for effective communication in a worldwide environment, higher education institutions should prioritize competency-based learning.